(untitled) (Revue El-Wahat pour les Recherches et les Etudes, 2026)
The current study aimed to identify the extent to which quality standards are applied in textbooks from the point of view of middle school teachers. The researcher used the descriptive approach. The textbook was highly rated in terms of (introduction, general form and style of output, content and method of presentation of the material, while the study did not indicate that there were statistically significant differences due to the experience variable in the teachers’ estimation of the quality of the textbook from their point of view.